2018
DOI: 10.4067/s0718-95162018005002801
|View full text |Cite
|
Sign up to set email alerts
|

Critical value of soil Olsen-P for potato production systems in volcanic soils of Chile

Abstract: The critical value of soil Olsen-P (mg Olsen-P kg-1) is the value of soil Olsen-P above which the probability of crop response to P fertilization is small or null. The aim of the present study was to determine the critical value of soil Olsen-P for potato tuber yield in volcanic soils. The data used in this study were taken from 41 experiments of P fertilization conducted in southern Chile from 1977 to 2015 by the National Potato Center at the Instituto de Investigaciones Agropecuarias (INIA). To identify the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 32 publications
(69 reference statements)
0
11
0
1
Order By: Relevance
“…For example, for phosphorus (P), critical values of soil Olsen-P have been defined for several crop species (Johnston et al 1986;Bollons and Barraclough 1999;Mallarino and Atia 2005;Colomb et al 2007). Recently, Sandaña et al (2018) found a critical value of 33 mg P kg −1 for potatoes grown in volcanic soils. Different critical values of soil Olsen-P for diverse sites could be related to differences in soil properties, such as soil texture (Redulla et al 2002;Johnston et al 2013;Sandaña et al 2018).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…For example, for phosphorus (P), critical values of soil Olsen-P have been defined for several crop species (Johnston et al 1986;Bollons and Barraclough 1999;Mallarino and Atia 2005;Colomb et al 2007). Recently, Sandaña et al (2018) found a critical value of 33 mg P kg −1 for potatoes grown in volcanic soils. Different critical values of soil Olsen-P for diverse sites could be related to differences in soil properties, such as soil texture (Redulla et al 2002;Johnston et al 2013;Sandaña et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Sandaña et al (2018) found a critical value of 33 mg P kg −1 for potatoes grown in volcanic soils. Different critical values of soil Olsen-P for diverse sites could be related to differences in soil properties, such as soil texture (Redulla et al 2002;Johnston et al 2013;Sandaña et al 2018). Regarding K, Li et al (2015) analysed a high number of trials assessing two rates of K in experiments conducted in Inner Mongolia, Gansu, Qinghai and Ningxia provinces, the main potato production regions in northwest China.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations